Impact of glycaemic control on fracture risk in 5368 people with newly diagnosed Type 1 diabetes: a time‐dependent analysis. Issue 8 (5th April 2019) - Thayakaran, R.; Perrins, M.; Gokhale, K. M.; Kumaran, S.; Narendran, P.; Price, M. J.; Nirantharakumar, K.; Toulis, K. A.
Abstract: Aims: To assess whether glycaemic control is associated with a lifelong increased risk of fracture in people with newly diagnosed Type 1 diabetes. Methods: People with newly diagnosed Type 1 diabetes between 1 January 1995 and 10 May 2016 were identified in The Health Improvement Network database. Longitudinal HbA1c measurements from diagnosis to fracture or study end or loss to follow‐up were collected. A Cox proportional hazards model with HbA1c included as a time‐dependent variable was fitted to these data. Results: Some 5368 people with newly diagnosed Type 1 diabetes were included. The estimated adjusted hazard ratio (aHR) for HbA1c was statistically significant [aHR 1.007; 95% confidence interval (CI) 1.002–1.011 (mmol/mol) and aHR 1.07; 95% CI 1.03–1.12 (%)]. An incremental higher risk of fracture was observed with increasing levels of HbA1c . Conclusions: In people with newly diagnosed Type 1 diabetes, higher HbA1c is associated with an increased risk for fractures. What's new?: Type 1 diabetes is associated with an increased incidence of fractures. The effect of glycemia is unknown, because change of glycaemic control over time has never been considered. HbA1c was associated with an increased fracture risk in people with newly diagnosed Type 1 diabetes (7% increments for each per cent increase in HbA1c ). This information may be considered in fracture risk assessment, and even in prompting early anti‐osteoporotic intervention in the context of Type 1 diabetes, especially when another established risk factor is present.